SNP-based non-invasive prenatal testing detects sex chromosome aneuploidies with high accuracy - Samango-Sprouse, Carole (2013)
OBJECTIVE: To develop a single nucleotide polymorphism- and informatics-based non-invasive prenatal test that detects sex chromosome aneuploidies early in pregnancy. METHODS: Fifteen aneuploid samples, including thirteen 45,X, two 47,XXY, and one 47,XYY, along with 185 euploid controls, were analyzed. Cell-free DNA was isolated from maternal plasma, amplified in a single multiplex PCR assay that targeted 19,488 polymorphic loci covering chromosomes 13, 18, 21, X, and Y, and sequenced. Sequencing results were analyzed using a Bayesian-based maximum likelihood statistical method to determine copy number of interrogated chromosomes, calculating sample-specific accuracies. RESULTS: Of the samples that passed a stringent quality control metric (93%), the algorithm correctly identified copy number at all five chromosomes in all 187 samples, for 934/935 correct calls as early as 9.4 weeks of gestation. We detected 45,X with 91.7% sensitivity (CI: 61.5-99.8%) and 100% specificity (CI: 97.9-100%), and 47,XXY and 47,XYY. The average calculated accuracy was 99.78%. CONCLUSION: This method non-invasively detected 45,X, 47,XXY, and 47,XYY fetuses from cfDNA isolated from maternal plasma with high calculated accuracies, and thus offers a non-invasive method with the potential to function as a routine screen allowing for early prenatal detection of rarely diagnosed yet commonly occurring sex aneuploidies.